A Generalization of the Concept of Cointegration to Harmonizable and Class (KF) Processes (European Journal of Pure and Applied Mathematics, 2010)
In this paper we consider the generalization of the concept of cointegration to non-stationary processes which are not necessarily I(d). Two cases are of special interest. First the case of non-stationary processes which adjust to an equilibrium not necessarily according to a linear adjustment process. Second the case of non-stationary (possibly I(1)) series which co-move according to a non linear or heteroscedastic adjustment process . The non-stationary processes considered here belong to the Kampé de Fériet (KF) class.